EXPRESSION OF PROHIBITION AS A REPRESENTATIF OF TABOO IN BADUY SOCIETY - Dase Erwin Juansah (LITERA, 2019)
EXPRESSION OF PROHIBITION AS A REPRESENTATIF OF TABOO IN BADUY SOCIETYAbstractThe use of prohibited expressions as a taboo representation is a linguistic and cult¬ural fact that is always present in every society. The taboo expression is considered to have a moral message for people who believe in it. This study aims to describe the expression of prohibition (pamali) as a taboo representation in the Baduy community. The study used a qualitative approach with ethnographic methods with anthropolinguistic design. The source of the research data is the informant's oral utterances in natural speech situations and what they are. Data collection with involved participation techniques, observations, and interviews. Analysis is carried out during collection, reduction, presenta-tion, and drawing conclusions/verification. Data analysis is inductive-qualitative. The study found that the prohibition expression in the Baduy community was classified into three categories. First, prohibited expressions relating to the management of agricultural land, including: (a) the time to start farming, (b) the process of farming, and (c) the time of harvesting rice in the fields. Secondly, the prohibition is related to the rules of community life, including: (a) the rules of life are personal, and (b) the rules of life are general. Third, the prohibition expressions related to the use of forest resources and the environment include: (a) rules relating to entrusted forests, and (b) rules for tillage. In general, the expression prohibition uses imperative forms, both orders and prohibitions.Keywords: expressions of prohibitions, taboos, imperatives of prohibitions and orders, Baduy communityUNGKAPAN LARANGAN SEBAGAI REPRESENTASI TABUPADA MASYARAKAT BADUYAbstrakPenggunaan ungkapan larangan sebagai representasi tabu merupakan fakta linguistik dan budaya yang selalu ada dalam setiap masyarakat. Ungkapan tabu dianggap memiliki pesan moral bagi masyarakat yang meyakininya. Penelitian ini bertujuan mendeskripsikan ungkapan larangan (pamali) sebagai representasi tabu di masyarakat Baduy. Penelitian menggunakan pendekatan kualitatif dengan metode etnografis berancangan antropolinguistik. Sumber data penelitian adalah tuturan lisan informan dalam situasi tutur yang alamiah dan apa adanya. Pengumpulan data dengan teknik partisipasi terlibat, pengamatan, dan wawancara. Analisis dilakukan selama pengumpulan, reduksi, penyajian, dan penarikan simpulan/verifikasi. Analisis data bersifat induktif-kualitatif. Penelitian menemukan bahwa ungkapan larangan pada masyarakat Baduy diklasifikasikan menjadi tiga kategori. Pertama, ungkapan larangan berkaitan dengan pengelolaan lahan pertanian, mencakup: (a) waktu mulai berladang, (b) proses berladang, dan (c) waktu panen padi di ladang. Kedua, ungkapan larangan berkaitan dengan aturan hidup bermasyarakat,  mencakup: (a) aturan hidup bersifat pribadi, dan (b) aturan hidup bersifat umum. Ketiga, ungkapan larangan berkaitan dengan pemanfaatan sumber daya hutan dan lingkungan, mecakup: (a) aturan berkaitan dengan hutan titipan, dan (b) aturan pengolahan tanah. Secara umum, ungkapan larangan menggunakan bentuk imperatif, baik perintah maupun larangan.Kata Kunci: ungkapan larangan, tabu, imperatif larangan dan perintah, masyarakat Baduy